Laboratory investigation of the properties of asphalt concrete mixtures modified with TOP-SBS - Ahmedzade, P.; Tigdemir, M.; Kalyoncuoglu, S. F. (Elsevier Sci Ltd, 2007)
Benefits of adding Tall oil pitch (TOP), Styrene-butadiene-styrene (SBS) and TOP + SBS to AC-10 in variant quantities to AC-10 were investigated. Initial research was done to determine the physical properties of asphalt cement and modifiers. Seven asphalt binder formulations were prepared with 8`% of TOP; 8 + 3, 8 + 6 and 8 + 9% of TOP + SBS, respectively; 3, 6 and 9% of SBS by total weight of binder. After that, Marshall samples were prepared by using the modified and unmodified asphalt binders. Additionally, compression strength test were done in different conditions to determine water, heat and frost resistance of all Marshall samples. Fatigue life and plastic deformation tests for Marshall samples (for different asphalt mixtures: modified and unmodified) were carried out using PC controlled repeated load indirect tensile test equipment developed at Suleyman Demirel University by Tigdemir (SDU-Asphalt Tester). The results of investigation indicate that asphalt mixture modified by 8% TOP + 6% SBS gives the best results in the tests that were carried out in this study, so that, this modification increases physical and mechanical properties of asphalt binder. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: asphalt cement; tall oil pitch; SBS; modified mixtures